Efektivitas Pembelajaran Berbasis Proyek (Project-Based Learning) Untuk Meningkatkan Prestasi Siswa Kelas XI A SMK Negeri 1 Wewewa Barat Tahun Pelajaran 2023/2024 Pada Mata Pelajaran Pemeliharaan Mesin Kendaraan Ringan - Abdul Malik, Suratman (BULLET : Jurnal Multidisiplin Ilmu, 2024)
This study aims to examine the effectiveness of the Project-Based Learning (PBL) method in improving student achievement in the Light Vehicle Engine Maintenance subject for Class XI A students at SMK Negeri 1 Wewewa Barat during the 2023/2024 academic year. The research was conducted in three stages: Pre-Cycle, Cycle I, and Cycle II, involving 36 students as research subjects.  In the Pre-Cycle stage, the average student score was 68.36, with a mastery percentage of 38.89%. The implementation of PBL in Cycle I showed an increase in the average score to 75.29, with the mastery percentage rising to 58.33%. Further implementation of PBL in Cycle II resulted in an even higher average score of 81.61, with the mastery percentage reaching 91.67%. These results indicate that the PBL method significantly improves student achievement in the subject studied.  This study concludes that the PBL method is effective in enhancing students' academic achievement, with a clear improvement from cycle to cycle. Although most students showed progress, there are still some who require additional guidance. The study recommends the continued implementation of the PBL method and the adjustment of strategies to assist students who have not yet achieved mastery.